Community Media Studies: An Overview. Issue 10 (25th October 2013) - Howley, Kevin
Abstract: This essay provides an overview of the field of community media studies. Like the study of "alternative media, " "citizens' media, " "independent, " and "radical" media – to mention but a few of the terms applied to participatory communication projects – academic inquiry into the structures, forms, and practices of community media has surged in recent years. While scholars often use these labels interchangeably, this essay focuses on academic and practitioner perspectives that explicitly and purposefully employ the term "community media." The overview identifies and briefly considers three prominent conceptual frameworks – media democratization, civil society, and the symbolic construction of community – which shape and inform this vibrant field of study. This overview concludes with some thoughts on the limits and possibilities of community media theory, and practice, in the new millennium.